Soft Skills Development in Indonesian Islamic Higher Education: Institutional Practices and the SSDIHE Model for Society 5.0 - Zulkifli Musthan; Dirman Dirman; Nasir Nasir; Ari Laksono (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
This study examines how leaders and lecturers at Islamic Higher Education Institutions in Indonesia conceptualize, implement, and evaluate soft skills development for students, with particular attention to its relevance in the Society 5.0 era. Employing a descriptive qualitative design, data were collected through in-depth interviews with institutional leaders and lecturers from thirteen PTKI representing diverse geographical and organizational contexts. Data were analyzed using thematic analysis to identify recurring patterns, strategic orientations, and institutional challenges. The findings indicate that soft skills development in PTKI is not treated as an auxiliary component of higher education, but as an integral dimension of Islamic educational objectives aimed at producing holistic graduates. Core soft skills emphasized across institutions include effective communication, teamwork, leadership, critical and reflective thinking, time management, and ethical integrity, all of which are framed within Islamic moral and spiritual values. The study further reveals that effective soft skills development relies on systematic curricular integration, experiential and project-based learning, participation in student organizations, and the strategic use of digital technologies. However, institutional constraints such as limited assessment instruments, uneven lecturer capacity, and the absence of standardized implementation frameworks remain significant challenges.